FAKTOR EKSPLOITASI MERANTI DI SUMATRA BARAT, KALIMANTAN BARAT DAN KALIMANTAN SELATAN - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1988)
A  study  on recovery in Meranti  logging operation  was carried out  in West Sumatra  and  West  Kalimantan  in 1984, and in South  Kalimantan  in 1985. The purpose of  this study  is to determine  recovery  figures for Meranti at  these particular locations, which may be use full  in the planning  efforts  of  logging companies.The  study  comes  to  the  following  conclusions   :Average  logging recovery for Meranti in West Sumatra, West Kalimantan and South  Kalimantan is 0.84.Recovery  among provinces  and among forest  companies  do not differ significantly,Recovery between diameter  classes differs significantly.  It  is suggested  that  logging of small diameter trees be done  with care, to avoid leaving relatively  small timber in the forest.